Novel Benzothiophene-Based Fluorescent Dye Exhibiting a Large Stokes Shift - Bolt, Yaroslav V.; Baleeva, Nadezhda S.; Nelyubina, Yulia V.; Andrianova, Anastasia A.; Kaskova, Zinaida M.; Tsarkova, Aleksandra S. (Synlett, 2021)
We report a simple two-step method for the synthesis of a novel highly fluorescent benzothiophene-based dye comprising five fused rings and exhibiting a large Stokes shift (Δλ = 152 nm or Δν = 5482 cm–1 in ethanol). Structural features of the obtained compound allow easy functionalization of the carbon core and open new possibility for the development of a series of new classes of fluorescent dyes.
Keywords: fluorescence; benzothiophenes; fluorescent dye; Stokes shift; oxidative coupling